Cloning and characterization of the sigA gene encoding the major sigma subunit of Rhizobium meliloti. - Rushing, B G (1995)
Using PCR to create a probe based on conserved region 2 of sigma factors, we have cloned the sigA gene coding for the major sigma factor of Rhizobium meliloti. The 684-residue protein encoded by the sigA gene was expressed in vitro in coupled transcription-translation experiments with R. meliloti extracts and migrated aberrantly in sodium dodecyl sulfate-polyacrylamide gel electrophoresis. Its deduced amino acid sequence is similar to that of RpoD of Escherichia coli and is nearly identical to that of SigA of the closely related bacterium Agrobacterium tumefaciens. Through Southern analysis, we located the gene on the R. meliloti main chromosome rather than on one of the megaplasmids. The sigA locus does not appear to be part of a macromolecular synthesis operon (MMS), as in many other bacterial species, but rather lies downstream of a partial open reading frame showing similarity to the threonine dehydrogenase gene (tdh) of E. coli.